The 2016 Who classification of central nervous system tumors: what neurologists need to know - DeWitt, John C.; Mock, Andreas; Louis, David N. (Current opinion in neurology, 2017)
Purpose of review The 2016 WHO classification of tumors of the central nervous system (2016 CNS WHO) features many changes that are relevant to neurologists treating patients with brain tumors as well as neurologists involved in basic, clinical, and epidemiological research. This review summarizes what neurologists need to know and will need to know in the next years. Recent findings The 2016 CNS WHO introduces diagnostic terms that ‘integrate’ histological and molecular information and suggests presenting diagnoses in a four-layered reporting format. In addition, it utilizes a ‘not otherwise specified’ designation to identify diagnostic categories that are not precisely defined. A better understanding of the biology of entities further led to changes in the tumor nosology, for example, diffuse gliomas based on IDH gene status. Meaningful molecular subgroups could also be identified in embryonal tumors and other entities. Given the pace of change in the field of brain tumor classification, there will likely be additional practical advances that emerge over the next few years. A new initiative entitled Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy intends to formulate recommendations between WHO updates. Summary The 2016 CNS WHO includes major changes in the way brain tumors are classified, with molecular parameters being incorporated into diagnostic criteria for a substantial number of such entities.